Sistem Informasi Administrasi CV Jaya Abadi - Hendra Kurniawan; Lily Puspa Dewi; Christian Purnama (Jurnal Infra, 2018)
At this time, the CV Jaya Abadi still record sales, purchase transactions, stock movement, and financial report manually. The CV Jaya Abadi still not using structured information systems. Owner often have difficulties of monitoring the amount of stock for each items. Recording process that still done manually often causes some errors that may disturb the business processes in car salon and waste a lot of time. Based on background of that problem on this CV Jaya Abadi, we designed a system that can process the operational data transactions, making of stock card and Stock, and making the complete financial reports. Application made by web-based program using Framework Laravel, PHP as programming tool and MySQl as database of the program. Record of Administration using perpetual method and card stock using Average.Results that obtained from the application that have been made, are able to record the transaction of sales and purchases, Stock that can set a reminder of the stock availability, accounting journal and report of financial statements that required.